2001
DOI: 10.1115/1.1371779
|View full text |Cite
|
Sign up to set email alerts
|

On Prediction of Thermal-Hydraulic Characteristics of Square-Sectioned Ribbed Cooling Ducts

Abstract: This paper presents the results of an investigation on prediction of local and mean thermal-hydraulic characteristics in rib-roughened ducts of square cross section. the Navier–Stokes and energy equations together with two low-Re k–ε turbulence models are solved numerically. The Reynolds turbulent stress tensor is calculated by two methods, namely, an eddy viscosity model (EVM) and an explicit algebraic stress model (EASM). The pressure–velocity coupling is handled by the SIMPLEC algorithm and calculations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The accurate prediction of these two curves is difficult to achieve because of the recirculation of flow near the ribs and the localized secondary flow effect. Many computational studies have attempted to correctly predict this smooth wall heat transfer effect using different turbulence models with little success (Ooi et al, 2002;Arts et al, 1997;Saidi and Sundén, 2001;Sleiti and Kapat, 2004). In the 180°bend region, a mass transfer experiment by showed results for a channel with geometry similar to that of the present study (e/D h = 0.094, P/ e = 10) with a Reynolds number of 30,000.…”
Section: Heat Transfer Augmentationmentioning
confidence: 68%
See 2 more Smart Citations
“…The accurate prediction of these two curves is difficult to achieve because of the recirculation of flow near the ribs and the localized secondary flow effect. Many computational studies have attempted to correctly predict this smooth wall heat transfer effect using different turbulence models with little success (Ooi et al, 2002;Arts et al, 1997;Saidi and Sundén, 2001;Sleiti and Kapat, 2004). In the 180°bend region, a mass transfer experiment by showed results for a channel with geometry similar to that of the present study (e/D h = 0.094, P/ e = 10) with a Reynolds number of 30,000.…”
Section: Heat Transfer Augmentationmentioning
confidence: 68%
“…Calculations using a number of different turbulence models by Arts et al (1997) showed that a three dimensional k-l model (similar to k-e) was not sufficient in predicting the secondary flows and an ASM was required. A comparison between an eddy-viscosity model (EVM) and an ASM reported that the average heat transfer on the side wall (which is most affected by secondary flows) was predicted to within 5%, but contours of the regions showed predictions that were completely different from what the experimental measurements showed (Saidi and Sundén, 2001). Jia et al (2002) employed an ASM and showed that the vertical rms value was overpredicted near the wall, but centerline heat transfer augmentation was still predicted well.…”
Section: Review Of Relevant Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Their studies showed that the k-e model failed to predict the flow accurately while the k-e-A model, which accounts for the anisotropy of turbulence, gave reasonable results. Saidi and Sunden (2001) also used k-e models in a periodic channel with inline orthogonal ribs, and the computations showed mixed results. Iacovides (1998) carried out computations using k-e and low-Re zonal differential stress models (DSM) in a periodic ribbed duct for stationary and rotating cases.…”
Section: Introductionmentioning
confidence: 94%
“…A vast number of numerical investigations have been performed to investigate the ability of numerical models, in particular turbulence models, to predict the heat transfer. Early research has mostly been conducted with the use of the Reynolds-averaged Navier-Stokes (RANS) method with a variety of turbulence models ranging from two-equation eddy-viscosity models such as the k-ε, k-ω SST, v 2 -f model and algebraic stress models, to full Reynolds stress closure with varying degrees of success [3][4][5][6][7][8][9][10][11][12]. In the last two decades, with increasing computational power and capacity, these efforts have transitioned to more advanced time-dependent methods such as large eddy simulations (LES) [13][14][15][16][17][18][19][20][21][22][23][24] and hybrid methods using unsteady RANS (URANS)-LES or detached eddy simulations (DES) [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%